The receptor‐like kinases GSO1 and GSO2 together regulate root growth in arabidopsis through control of cell division and cell fate specification. Issue 2 (13th November 2013) - Racolta, Adriana; Bryan, Anthony C.; Tax, Frans E.
ABSTRACT Background: The root apical meristem of Arabidopsis is established post‐embryonically as the main source of root cells, and its activity is maintained by complex bidirectional signaling between stem cells and mature cells. The receptor‐like kinases GASSHO1 (GSO1) and GSO2 have been shown to regulate aerial epidermal function and seedling growth in Arabidopsis. Results: Here we show that gso1; gso2 seedlings also have root growth and patterning defects. Analyses of mutant root morphology indicate abnormal numbers of cells in longitudinal files and radial cell layers, as well as aberrant stem cell division planes. gso1; gso2 double mutants misexpress markers for stem cells and differentiated root cell types. In addition, gso1; gso2 root growth defects, but not marker missexpression or patterning phenotypes, are rescued by growth on media containing metabolizable sugars. Conclusions: We conclude that GSO1 and GSO2 function together in intercellular signaling to positively regulate cell proliferation, differentiation of root cell types, and stem cell identity. In addition, GSO1 and GSO2 control seedling root growth by modulating sucrose response after germination. Developmental Dynamics 243:257–278, 2014. © 2013 Wiley Periodicals, Inc.